On Exploration of Pestle Analysis on Coffee Industry and Studying the Hierarchical Inter-relationships amongst the Barriers Faced by Tea and Coffee Industry in India - Aggarwal, Lakshay; Aggarwal, Remica (Contemporary Research in Business, Management and Economics Vol. 7, 2024)
Out of the world’s total tea production, 27% is being done by Indians. As India is one of the countries with largest consumer base for tea, nearly 75 percent of the country’s total produce is consumed by the local people. Indian tea has its own taste and quality that makes it stand out in the market. Coffee is a hot beverage that is liked by Indians for more than 500 years now. Known and loved the world over, this drink represents an industry worth over $100 billion. The present research work focuses on doing PESTLE analysis on the tea and Coffee industry and also explores the challenges faced by both the prime beverages market and tries to explore further the hierarchical inter-relationships amongst them using ISM methodology.